The Scale Effects Of Tourism Accommodation On Regional Development - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Studi Wanita UGM, 2005)
ABSTRAK The relationship between tourism and regional development is a complex phenomenon. It can be defined and viewed from different ways and several perspectives but essentially they are basically derived from the two core concepts: tourism and development. This is especially true with the trend towards an increasing scale of tourism enterprises in key sectors such as accommodation, which in turn reflects the increasing diversity of different sectors in the tourism industry. Due to these intricate realities, tourism in developing countries cannot be approached just within a _framework of master planning or marketing